Feasibility and safety of enzymatic debridement for the prevention of operative escharotomy in circumferential deep burns of the distal upper extremity - Fischer, Sebastian; Schmidt, Volker-Jürgen; Hirche, Christoph (Surgery, 2019)
Background - Burn-induced compartment syndrome is a severe sequela after circumferential burns of the extremities and is avoidable by immediate release of the underlying pressure under the eschar. Although the current gold standard is operative escharotomy, this procedure carries considerable morbidity. Our study evaluates the safety and effectiveness of immediate enzymatic debridement to prevent the need for operative escharotomy because of burn-induced compartment syndrome in selected patients. - Patients and Methods - From 2015 to 2017, all patients suffering from deep circumferential burns of the upper extremities requiring operative escharotomy were potential candidates for the treatment algorithm evaluated by this study. Exclusion criteria involved burn trauma > 12 hours, clinically established burn-induced compartment syndrome, intolerance to the enzymatic debriding agent, dry burns requiring presoaking, as well as blast and electrical injuries requiring fasciotomy or carpal tunnel release. All patients with the inclusion criteria received enzymatic debridement with Nexobrid immediately after admission to our burn center. Enzymatic debridement was applied according to the manufacturer's recommendations. After enzymatic debridement, extremities were revisited every 2 hours for 24 hours to determine the need for conversion to conventional operative escharotomy. The indication for and time to skin grafting was reviewed, and functional outcomes assessed during follow-up examination. - Results - Included in this sturdy were 13 patients with 20 burned upper extremities. Enzymatic debridement provided a sufficient eschar removal in all patients. Conversion to conventional operative escharotomy was thus not necessary in any patient. Secondary skin grafting was required in 9 patients. Functional outcomes were favorable 11.9 months after burn trauma. - Conclusion - If the specific contraindications are respected, enzymatic debridement is safe and effective for the prevention of burn-induced compartment syndrome after deep circumferential burns at the upper extremity, and thus making operative escharotomy unnecessary.
Gesehen am 11.11.2019